First Steps towards Hybrid Forms of Service Provision in Municipalities - Satu Aaltonen; Tanja Lepistö; Ulla Hytti (United Kingdom, 2022)
Topic – In many western countries there is an ongoing move from progressive public administration to new public management (NPM) and currently even further towards new public governance (NPG). NPG entails increasing importance of collaborative networks, more emphasis on the inter-organizational processes and paying more attention on the citizen satisfaction. This transition brings along also more hybrid forms of public service provision, a change in the governance logics as well as the roles of different actors such as states, municipalities, private companies and third sector organisations.
Aim – This paper aims to point out factors supporting and hindering the early stages of a transition towards hybrid forms of service provision and New Public Governance (NPG) in a municipality context.
Methodology – The context of our case study is development projects taking place in two municipalities in Finland. Finland is currently undergoing the largest top-down reform on the regional level administrative structures and practices ever, which offers us a unique platform to study the social processes towards hybridity and NPG.
Contribution – Even if there is a long history of studying hybridization, the focus has seldom been on the process that leads to it. Our focus in this on-going study is in the early phases of this cumbersome process, where both segregating and blending mechanisms operate in tandem and create many kinds of tensions.
Implications for policy and practice – Public governance has been in a continuous flux already some decades in parallel to the increase in austerity talk, consumerism and structural changes in service provision. From a standpoint of entrepreneurship it is important to understand these processes since public governance outcomes and practices are creating the policy context and business opportunities for SMEs and the role of businesses is changing as the process proceeds.
ISBE 2018 Conference Proceedings